The Power of Contribution and Attribution in Assessing Educational Outcomes for Individuals, Teams, and Programs. (July 2020) - Schumacher, Daniel J.; Dornoff, Eric; Carraccio, Carol; Busari, Jamiu; van der Vleuten, Cees; Kinnear, Benjamin; Kelleher, Matthew; Sall, Dana R.; Warm, Eric; Martini, Abigail; Holmboe, Eric
Abstract : Recent discussions have brought attention to the utility of contribution analysis for evaluating the effectiveness and outcomes of medical education programs, especially for complex initiatives such as competency-based medical education. Contribution analysis focuses on the extent to which different entities contribute to an outcome. Given that health care is provided by teams, contribution analysis is well suited to evaluating the outcomes of care delivery. Furthermore, contribution analysis plays an important role in analyzing program- and system-level outcomes that inform program evaluation and program-level improvements for the future. Equally important in health care, however, is the role of the individual. In the overall contribution of a team to an outcome, some aspects of this outcome can be attributed to individual team members. For example, a recently discharged patient with an unplanned return to the emergency department to seek care may not have understood the discharge instructions given by the nurse or may not have received any discharge guidance from the resident physician. In this example, if it is the nurse's responsibility to provide discharge instructions, that activity is attributed to him or her. This and other activities attributed to different individuals (e.g., nurse, resident) combine to contribute to the outcome for the patient. Determining how to tease out such attributions is important for several reasons. First, it is physicians, not teams, that graduate and are granted certification and credentials for medical practice. Second, incentive-based payment models focus on the quality of care provided by an individual. Third, an individual can use data about his or her performance on the team to help drive personal improvement. In this article, the authors explored how attribution and contribution analyses can be used in a complimentary fashion to discern which outcomes can and should be attributed to individuals, which to teams, and which to programs.